Asymmetric structure and domain binding interfaces of human tyrosyl‐tRNA synthetase studied by molecular dynamics simulations. Issue 2 (11th January 2013) - Savytskyi, Oleksandr V.; Yesylevskyy, Semen O.; Kornelyuk, Alexander I.
<x xml:space="preserve">Abstract</x> Human tyrosyl‐tRNA synthetase (HsTyrRS) is composed of two structural modules: N‐terminal catalytic core and an EMAP II‐like C‐terminal domain. The structures of these modules are known, but no crystal structure of the full‐length HsTyrRS is currently available. An all‐atom model of the full‐length HsTyrRS was developed in this work. The structure, dynamics, and domain binding interfaces of HsTyrRS were investigated by extensive molecular dynamics (MD) simulations. Our data suggest that HsTyrRS in solution consists of a number of compact asymmetric conformations, which differ significantly by their rigidity, internal mobility, orientation of C‐terminal modules, and the strength of interdomain binding. Interfaces of domain binding obtained in MD simulations are in perfect agreement with our previous coarse‐grained hierarchical rotations technique simulations. Formation of the hydrogen bonds between R93 residue of the ELR cytokine motif and the residues A340 and E479 in the C‐module was observed. This observation supports the idea that the lack of cytokine activity in the full‐length HsTyrRS is explained by interactions between N‐modules and C‐modules, which block the ELR motif. Copyright © 2013 John Wiley & Sons, Ltd.